Postoperative Respiratory Complications in Patients at Risk for Obstructive Sleep Apnea: A Single-Institution Cohort Study. (July 2017) - Ramachandran, Satya Krishna; Pandit, Jaideep; Devine, Scott; Thompson, Aleda; Shanks, Amy
Abstract : BACKGROUND: Obstructive sleep apnea (OSA) is a prevalent condition that is associated with early postoperative respiratory complications (PRCs). As the majority of patients with OSA are undiagnosed, preoperative screening remains the most efficient method to identify suspected OSA. METHODS: This retrospective study was performed on patients undergoing anesthesia in a single academic medical center. We assigned OSA risk class retrospectively to all patients in the study by using the Perioperative Sleep Apnea Prediction (PSAP) score. We evaluated the relationship between PSAP categories and early postoperative invasive airway placement after adjusting for several preoperative and intraoperative factors (including surgical risk) previously associated with PRC occurrence. RESULTS: A total of 108, 479 patients were included in the final analysis with an incidence of PRC was 0.3% (n = 280). High PSAP score was associated with postoperative intubation (adjusted odds ratio, 2.3; 95% confidence interval, 1.5–3.7). Several risk factors reflecting anesthetic agents, neuromuscular blocking agents, and opioids were also independently associated with early PRC. CONCLUSIONS: We report that suspected OSA based on the PSAP score is independently associated with increased risk of early PRC. Specific anesthetic agents are independently associated with early PRC, pointing to the potential for examining risk modification through these exposures in future studies.